The interaction of meso and macro contexts with students’ careers. Three applied analysis - Decataldo, Alessandra; Amico, Andrea; D’Alessandro, Giampiero (Central European Journal of Educational Research, 2019)
This paper presents three applied analysis. Our principal interest is to understand how meso (university level) and macro (national level) contexts interact with micro phenomena such as students’ careers. To achieve this aim, the paper shows a secondary analysis of longitudinal administrative data by means of Sequence Analysis and Event History Models. Furthermore, it shows the results of an additional analysis using a quasi-experimental research on longitudinal data.The paper examines typical pathways of Italian students, by means of administrative information’s on student enrollment from Sapienza University of Rome. The aim of this paper is triple: 1. describe students’ careers in higher education by building a typology of pathways using Sequence Analysis. 2. Identify how socio-economic and macro level characteristics affect students’ careers by multinomial logistic regression model where clusters are used as dependent variables and focus on the study of the “event” by using Event History analysis. 3. Evaluate the Italian Higher Education reform policies and their main outcomes throughout a quasi-experimental research.Mainly, the outcomes show the importance of the warming-up period, the individual choice and the exogenous events after enrolment in determining the success/failure of each career. Our outcomes suggest that Italian universities should rethink the mechanisms available to manage failure and guide student choices.